Characterization of Collagen (IV) mRNA in Cell Lines of Breast Cancer - Mat Yusof , Afzan; Mohammad , Mardhiah; Syed Bahrom, Sharifah Norbaizura; Mohideen, Syahirah Kaja; Roshdi, Ridhwan; Parman, Adibah (Penerbit UTM Press, 2015)
Breast cancer incidence rate has increased in the 5 recent years with 14% increases in mortality. The structural change in the collagen chain has led to alterations in the cancer cells. Various biological processes, such as differentiation or gene expression, are regulated through extracelullar matrix (ECM)[1]. The restructuring of the collagenous architecture in the hypoxic microenvironment may influence the invasive growth of the cancer cells. With the increased stress within the cell, the invasion of cancer cells into the ECM was triggered. This cell lines model would enable the exploration of the relationship between the extracellular matrices component and the tumor proliferation. The aim of this study is to characterize the collagen (IV) mRNA expression in the breast cancer cell. Breast cancer (MCF7) cell lines were cultured and harvested upon confluent. The RNA was extracted from the cell lines and then the cDNA were synthesized. The collagen (IV) mRNA levels in breast cancer cell lines were measured using real time PCR and GAPDH was used as an internal control. The level of COL4A2 (IV) mRNA expression was higher compared with COL4A1 (IV) mRNA. The level of COL4A5 (IV) mRNA was reduced significantly in breast cancer cells lines. Overall, the expression of COL4A1-A6 (IV) was reduced. The reduced amount of collagen (IV) in breast cancer cell lines suggested that the collagen was restructured and this has triggered the tumor invasion into the ECM.